Afforestation and gardening in Municipal School of Basic Education Assis Brasil Palmeira das Missões–RS - Fagundes, Joice Feil; Bandeira, Giseli Luisa; Siqueira, André Boccasius; Neis, Franciele Antonia; Konflanz, Tais Lazzari (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The purpose of this project was to sensitize and motivate children/students of school municipal assis brasil located in palmeira das missões/rs, working in teams, preserve and organize the school environment. The issue revolved around improving the environmental quality of the area frequented by students and therefore the work of afforestation and gardening outside the school aimed to leave the pleasant and recreational site, since much of the time students stay in this space. So that the school community can have better harmony with the natural environment is vital to have an organized and aesthetically pleasing space. Therefore, it is important to develop projects to create a suitable and warm, it is the duty of the school community to prepare citizens for a humane social life and harmonized with the environment.